Comparison of feeding practices, eating behaviors and dietary intake between children with Autism Spectrum Disorder of different body weight status in Sarawak - W. Y., Gan; L. S., Law; W. L., Cheah
Individuals with Autism Spectrum Disorder (ASD) are a nutritionally vulnerable population. To date, information on nutritional status and dietary intake of Malaysian children with ASD is scarce. This cross-sectional study aimed to compare parental feeding practices, child eating behaviors, and dietary intake between children with ASD of different body weight status from 16 autism intervention centers in Sarawak. A total of 124 children (83.9% males and 16.1% females) aged 2 to 11 years and their mothers were recruited using convenience sampling. Mothers were interviewed to obtain information on parental feeding practices and child eating behaviors. Anthropometric measurements including weight and height were measured by the researcher. Dietary intake was assessed using food diary and nutrient intakes were compared with the Malaysian Recommended Nutrient Intakes (RNI). The prevalence of at risk of overweight (4.8%), overweight (16.9%), and obesity (20.2%) was higher than that of thinness (3.2%). Inadequate intake of energy (33.9%), calcium (90.3%), vitamin C (37.9%), vitamin A (52.4%), and vitamin D (93.5%) was reported among children with ASD. Mothers with overweight/obese children reported higher scores in perceived child weight (p<0.001), concern about child weight (p=0.003), food responsiveness (p=0.001), emotional over-eating (p=0.035), and enjoyment of food (p=0.038) subscales as compared to their counterparts with normal weight. Overweight/obese children with ASD consumed more energy, fat, and iron than normal weight children with ASD (p<0.05). Children with ASD in this study were prone to overnutrition and nutritional deficiencies. Dietary interventions and trainings on parental feeding practices should be included in the intervention programmes by the autism intervention centers to improve feeding practices, eating behaviors, and nutrient intakes of children with ASD.